Lymphocytes influence Leishmania major pathogenesis in a strain-dependent manner. - Md Abu Musa; Risa Nakamura; Asma Hena; Sanjay Varikuti; Hira L Nakhasi; Yasuyuki Goto; Abhay R Satoskar; Shinjiro Hamano (Public Library of Science (PLoS), 2019)
Cutaneous leishmaniasis (CL) is the most common form of leishmaniasis and is caused by several species of Leishmania parasite. Clinical presentation of CL varies from a self-healing infection to a chronic form of the disease determined by the virulence of infecting Leishmania species and host immune responses to the parasite. Mouse models of CL show contradictory roles of lymphocytes in pathogenesis, while acquired immune responses are responsible for host protection from diseases. To reconcile the inconclusive roles of acquired immune responses in pathogenesis, we infected mice from various genetic backgrounds with two pathogenic strains of Leishmania major, Friedlin or 5ASKH, and assessed the outcome of the infections. Our findings showed that the genetic backgrounds of L. major determine the impact of lymphocytes for pathogenesis. In the absence of lymphocytes, L. major Friedlin induced the lowest inflammatory reaction and pathology at the site of infection, while 5ASKH infection induced a strong inflammatory reaction and severe pathology. Lymphocytes ameliorated 5ASKH mediated pathology, while it exacerbated pathology during Friedlin infection. Excess inflammatory reactions, like the recruitment of macrophages, neutrophils, eosinophils and production of pro-inflammatory cytokines, together with uncontrolled parasite growth in the absence of lymphocytes during 5ASKH infection may induce severe pathology development. Taken together our study provides insight into the impact of differences in the genetic background of Leishmania on CL pathogenesis.